In vitro fertilization outcomes in women with polycystic ovary syndrome: A meta-analysis. (April 2021) - Tang, Kefu; Wu, Lei; Luo, Ying; Gong, Bo
Abstract: Objective: During the past three decades, applying IVF for infertility treatment PCOS women has increased significantly, and the landscape of treatment strategies has changed dramatically. However, early review of IVF on PCOS have insufficiently accounted for efficacy and safety of the technic. With abundant studies in recent years, there is a need to reconcile these new data. Material and methods: To compare reproductive and obstetric outcomes of IVF between women with and without PCOS, a meta-analysis of 95 studies involving more than 21289 PCOS patients and 43036 controls was performed. Results: Despite longer stimulation duration (WMD = 0.34 day, 95 % CI: 0.09, 0.59) and lower dose of Gn required (WMD = -361.3 IU, 95 % CI: -442.3, -280.4), more oocytes (WMD = 3.67, 95 % CI: 3.14−4.21) and matured oocytes (WMD = 2.16, 95 % CI: 1.52−2.80) per cycle were obtained from PCOS women. There were no statistically significant differences for cleavage, high-grade embryo and implantation rate. Although similar pregnancy and live birth rates per cycle were achieved in PCOS and non-PCOS women after IVF, women with PCOS still suffered from significantly increased risks of miscarriage (OR = 1.44, 95 % CI: 1.20−1.72), biochemical pregnancy loss (OR = 1.89, 95 % CI: 1.48−2.41), and OHSS (OR = 3.58, 95 % CI: 2.86−4.48), in addition to lower fertilization rate (OR = 0.79, 95 % CI: 0.71−0.88). Adverse obstetric outcomes including ectopics pregnancy and multiple pregnancies are comparable between two groups. The overall cycle cancellation rate was significantly higher among PCOS women with OR of 2.55 (95 % CI: 1.67−3.89), and concern over OHSS or hyper-response constitute the main cause. Similar results were also observed after stratified analysis. Conclusions: Our results support the effectiveness of IVF for infertility treatment among PCOS patients. However, options to minimize adverse outcomes regarding to lower fertilization, miscarriage, biochemical pregnancy loss and OHSS are required. Further studies elucidating detailed mechanism underlying these adverse outcomes could be of great importance to improve the experience of IVF treatment.